How Well Do Jurors Reason? Competence Dimensions of Individual Variation in a Juror Reasoning Task - Kuhn, Deanna; Weinstock, Michael; Flaton, Robin (Psychological Science, 1994)
Significant individual variation is observed in how people reason as jurors At the satisficing end of a continuum we identify, the juror draws on evidence selectively to construct a single story of what happened, with no acknowledgment of discrepant evidence or alternative possibilities A contrasting theory-evidence coordination mode of processing entails construction of multiple theories (story-verdict constellations) that are evaluated against the evidence and against alternatives Individual differences influence task outcome, the satisficing mode being associated with more extreme verdict choices and very high certainty